2019
DOI: 10.12659/msm.916918
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Chloride-Releasing 3D Printed Scaffold for Enhanced Cartilage Regeneration

Abstract: Background We synthetized a 3D printed poly-ɛ-caprolactone (PCL) scaffold with polydopamine (PDA) coating and lithium chloride (LiCl) deposition for cartilage tissue engineering and analyzed its effect on promoting rabbit bone marrow mesenchymal stem cells (rBMSC) chondrogenesis in vitro . Material/Methods PCL scaffolds were prepared by 3D printing with a well-designed CAD digital model, then modified by PDA coating to produce PCL-PDA scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…[30] Lower contact angle showed better hydrophilicity, as rBMSCs and chondrocytes were cultured in an aqueous environment. [2] Our results show that the incorporation of PDA and PLGA nanoparticles into the PCL scaffold significantly decreased the contact angle of the pure PCL which can provided a much better biomimetic extracellular matrix (ECM) microenvironment. While the pore size, porosity and compressive strength were retained, which provide an appropriate pore space to facilitate cell infiltration and nutrition supply, and is suitable to withstand the forces on the joint.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…[30] Lower contact angle showed better hydrophilicity, as rBMSCs and chondrocytes were cultured in an aqueous environment. [2] Our results show that the incorporation of PDA and PLGA nanoparticles into the PCL scaffold significantly decreased the contact angle of the pure PCL which can provided a much better biomimetic extracellular matrix (ECM) microenvironment. While the pore size, porosity and compressive strength were retained, which provide an appropriate pore space to facilitate cell infiltration and nutrition supply, and is suitable to withstand the forces on the joint.…”
Section: Discussionmentioning
confidence: 79%
“…As cartilage is a tissue with poor capacity of regeneration, cartilage tissue engineering offers the ability to repair cartilage by combining cells, scaffolds, and signals. [1,2] Insulin-like growth factor-1 (IGF-1) has been extensively researched for its ability to encourage cell proliferation, inhibition of cell apoptosis, and anabolic effects on musculoskeletal tissues. [3][4][5][6][7][8] It has been demonstrated that IGF-1 is an anabolic growth factor that is very important in cartilage development and homeostasis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was most likely that Li + ions in L2C4S4 played the principal role. As previous studies have shown that Lireleasing biomaterials could induce chondrogenic differentiation, hyaline cartilaginous matrix formation [33] and enhance cartilage regeneration [34], our L2C4S4 bioceramics is also expected to be applicable to clinical cartilage repair due to the good release capacity of Li + ions.…”
Section: Discussionmentioning
confidence: 92%